Factors that influence customer satisfaction in 3-star hotels in kelantan - Kasturi A/P Ragunathan; Lee Sook Yee; Melissa Anak Henry; Mohamad Asri Zulkifli Amin (2022)
A large range of service-related industries recognise as the "hospitality industry" includes housing, food and beverage services, event organizing, theme parks, travel agencies, tourism, hotels, restaurants, and bars. In the context of hospitality terms, accommodation is a building or place that us available for certain people, things, and activities. The accommodation such as hotels main to provides space and room for someone to stay, live, or work in. In this study, the researcher examines the factors that influence customer satisfaction in 3-star hotels in Kelantan. Besides, this research is ti study the relationship between service quality and customer satisfaction. In conducting this research, a survey was conducted by using questionnaires through google form, involving 384 respondents of travelers in Malaysia. A Descriptive, Reliability, and Inferential analysis were used to analyze data obtained. Findings revealed that three variables are significantly related to customer satisfaction. This research can provide suggestions and enlightenment for future research. Keyword: Hospitality industry, Hotels, Customer Satisfaction